Variant Guillain-Barré Syndrome in a Patient with Non-Hodgkin’s Lymphoma - R. H. Bishay; J. Paton; V. Abraham (Case Reports in Hematology)
We report a 72-year-old female patient with diffuse large B cell non-Hodgkin’s lymphoma (NHL) with previous treatment with standard chemotherapy presenting as an acute, ascending, sensorimotor polyneuropathy. Nerve conduction studies and lumbar puncture supported a rare, but ominous, axonal variant of Guillain-Barré Syndrome (GBS) known as acute motor and sensory axonal neuropathy (AMSAN), which is distinguished from the more common, acute demyelinating forms of GBS. Previous reports have largely focused on toxicities secondary to chemo- or radiotherapy as a major contributor to the development of acute neuropathies in malignancy. Clinicians should also be mindful of direct neoplastic invasion or, less commonly, paraneoplastic phenomenon, as alternative mechanisms, the latter possibly reflecting immune dysregulation in particularly aggressive lymphomas. At the time of writing, this is the first report in the literature of an axonal variant of GBS in a patient with diffuse large B cell NHL. A discussion regarding common and uncommon neuropathies in haematological malignancies is made, with a brief review of the anecdotal evidence supporting a paraneoplastic association with GBS or its variant forms in the setting of lymphoma.